2009
DOI: 10.1118/1.3183820
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of ionization chambers for the relative dosimetry of kilovoltage x‐ray beams

Abstract: In this work, the authors have evaluated ten different ionization chambers for the relative dosimetry of kilovoltage x-ray beams in the energy range of 50-280 kVp. Percentage depth doses in water and relative detector response (in Solid Water and in air) were measured for each of the x-ray beams studied using a number of chambers. Measured depth dose data were compared with Monte Carlo calculated depth doses using the EGSnrc Monte Carlo package and the BEAMnrc user code. The accuracy of the phase space files g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 53 publications
2
83
0
22
Order By: Relevance
“…This implies that the combination of lower Z and higher density in case of the PTW Semiflex chambers results in a similar photoelectric absorption for chambers of comparable volume. The results for the Semiflex chamber PTW 31013 are consistent with the results from the previous study by Hill et al (20) who reported a variation of 11% for an energy range up to 280 kVp.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This implies that the combination of lower Z and higher density in case of the PTW Semiflex chambers results in a similar photoelectric absorption for chambers of comparable volume. The results for the Semiflex chamber PTW 31013 are consistent with the results from the previous study by Hill et al (20) who reported a variation of 11% for an energy range up to 280 kVp.…”
Section: Resultssupporting
confidence: 91%
“…All investigated detectors, except the parallel plate chambers, possess rotation‐symmetric designs, which is crucial for CT dosimetry. The parallel plate chambers were included in this study for comparison with previous studies 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations